Perspektif Peer Assessment sebagai Model Evaluasi Autentik dalam Pendidikan Agama Islam - Mahrusah, Luthfiyah; Fariza Anjani; Ahmad Munzir (Prodi Pendidikan Agama Islam, 2025)
The implementation of PAI learning assessment is still dominated by a traditional one-way evaluation model from lecturers to students, which does not encourage active, reflective, and participatory involvement. This situation is not in line with the principles of authentic assessment, which emphasizes the importance of student involvement in the assessment process. This study aims to explain the implementation of peer assessment in PAI learning, including its benefits, perceptions, and challenges. Using qualitative methods and case studies, data were collected through in-depth interviews with one lecturer and four PAI students, classroom observations, and documentation. The analysis was conducted thematically with the help of the NVivo 12 application to identify the main themes. The results show that peer assessment provides a new, more participatory and reflective experience for students. The benefits include the development of learning styles, increased creativity, critical thinking skills, and learning motivation. However, this study found several obstacles in the form of friendship bias, reluctance to give criticism, and differences in understanding of the rubric, which affect the objectivity of the assessment. For lecturers, clarity of assessment instruments is considered an important factor for successful implementation. Overall, peer assessment has been proven to contribute to improving the quality of Islamic Religious Education while shaping critical, reflective, and responsible attitudes in students. This study emphasizes the ethical and emotional dimensions of peer assessment practices, which show that peer assessment is not only an academic tool but also a means of shaping Islamic character based on the values of honesty, justice, and trust. Keywords: Peer Assessment, Authentic Assessment, Islamic Religious Education, Learning Motivation.